On the Reliability and Factorial Validity of the Assessment Scale for Creative Collaboration - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2019)
Creativity, a primary objective across academic disciplines, has received considerable attention over the past few decades. While much focus has been put on the measurement of individual creativity, a notable research gap remains regarding social collaborative creativity that occurs in blended learning settings. This work offers an initial validation of the psychometric properties of a self-reported instrument, the Assessment Scale for Creative Collaboration (ASCC) that can measure learner perceptions of creative collaboration in a team within a computer-supported collaborative learning (CSCL) context. In this study, 236 undergraduate and graduate students rated the key variables of creative collaboration. Exploratory factor analysis resulted in a three-factor scale (21 items) measuring ‘Synergistic Social Collaboration’, ‘Distributed Creativity’ and ‘Learning Regulation and Achievement’. Cronbach’s alphas indicated good internal consistency for the subscales. An instrument with psychometric properties for the assessment of creative collaboration is much-needed for the growing community of researchers and practitioners looking into creativity in education. It is also critical in advanced technical subjects, such as Design, HCI and Engineering, where collaboration is essential in developing innovative products.
Keywords: Blended learning; Psychometric measure; Creative Collaboration